Mutu Kinerja Tenaga Pendidik (Guru) Dalam Manajemen Pendidikan Era Pandemic Covid-19 - Khairiah Khairiah; Muhammad Nor Hidayat; Indah Kurnia; Mutiara Harmaida; Ibnu Rusydi; Warto Warto (UIN Fatmawati Sukarno Bengkulu, 2021)
Abstract: The era of the covid-19 pandemic in education management shows a threat to the quality of the performance of educators. Some educators show work behavior in line with existing standards and codes of ethics, and some other educators show difficulties in working. In line with this, the purpose of this paper is not only to map the form of performance quality conditions in various groups of educators, but also to analyze the reasons for the decline in the quality of teacher performance. This paper is based on data collected from various online data sources by taking into account the structural characteristics of groups of educators. The results of this study show that group differences and the abilities of educators have become a force that structures the behavior of educators' performance on the threat to the quality of educators' performance in education management during the covid-19 pandemic. Thus, it can be concluded that the quality of the performance of educators in the management of education has become an important factor in the reality of the quality of education in the era of the covid-19 pandemic. And it can be suggested, it is necessary to expand cases, and add sources of data to be researched, so that it is possible to understand the impact of the COVID-19 pandemic in the world of education in depth and comprehensively.Keywords: Pandemic Covid-19 Era, Education Management, Quality Performance of Educators Abstrak: Era pandemic covid-19 dalam manajemen pendidikan memperlihatkan ancaman mutu kinerja tenaga pendidik. Sebagian tenaga pendidik memperlihatkan perilaku kerja sejalan dengan standar dan kode etik yang ada, dan sebagian tenaga pendidik yang lain memperlihatkan kesulitan dalam bekerja. Sejalan dengan hal tersebut, tujuan tulisan ini selain memetakan bentuk kondisi mutu kinerja dalam berbagai kelompok tenaga pendidik juga menganalisis alasan-alasan terjadinya penurunan mutu kinerja tenaga pendidik. Tulisan ini didasarkan pada data yang dikumpulkan dari berbagai sumber data online dengan memperhatikan karakteristik structural kelompok tenaga pendidik. Hasil penelitian ini memperlihatkan bahwa perbedaan kelompok dan kemampuan para tenaga pendidik telah menjadi kekuatan yang menstrukturkan perilaku kinerja tenaga pendidik atas ancaman mutu kinerja tenaga pendidik dalam manajemen pendidikan selama pandemic covid-19. Dengan demikian dapat disimpulkan bahwa mutu kinerja tenaga pendidik dalam pengelolaan pendidikan telah menjadi faktor penting atas suatu realitas mutu pendidikan di era pandemic covid-19. Dan dapat disarankan, perlu perluasan kasus, dan penambahan sumber data yang diteliti, sehingga memungkinkan dapat dipahami dampak pandemic covid-19 dalam dunia pendidikan secara mendalam dan komprehensif. Kata Kunci: Era Pandemic Covid-19, Manajemen Pendidikan, Mutu Kinerja Tenaga Pendidik